The first stop of transit migrant students on the road to Europe and America: The Turkish education system - Icen, Mustafa; Oruc, Sahin; Seker, Mustafa (FRONTIERS MEDIA SA, 2022)
There have been forced migrations from one country to another due to wars, conflicts, and various reasons within and among countries. Turkey is a transit point from Asia to Europe. Accordingly, this study sheds light on experiences the refugee students have in the Turkish Education System. Therefore, this study is meant to be based on a qualitative approach as a case study method. The data were obtained through a semi-structured interview and a focus group interview. The information was gathered from nine students-three Syrians, two Iranians, two Iraqis, and two Afghans-as well as five teachers. According to the results, refugee students had difficulty learning and using a new language, adapting to a new country and environment, and getting used to new friends they made and teachers they were taught by. The results also indicate that students were concerned about their inability to travel to the United States and European countries.
Keywords: education; multicultural education; refugee student; transit migrant; Turkish education system; Psychology